Digitalisasi Kearifan Lokal Aceh melalui Pop-Up Book Digital dalam Pembelajaran Pancasila Sekolah Dasar - Ayudia, Inge (Universitas Muhammadiyah Magelang, 2026)
This study aims to develop a digital pop-up book learning media based on Aceh local wisdom in Pancasila education for elementary school students. The bacground of this research is the lack of innovative and contextual learning media that integrates local cultural values into classroom learning. This study uses a research and development (R&D) approach with the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The results indicate that the developed media is highly valid (90.75%), practical (90%), and effective, with a significant improvement in students learning outcomes (from 60 to 85). The results show that the developed media is valid, practical, and effective in improving students understanding of Pancasila values and civic awareness. The integration of Aceh local wisdom in digital pop-up book media provides meaningful learning experiences and strengthens students cultural identity. Thus, this media is suitable to be used as an alternative learning tool in elementary schools. Keywords: digital pop-up book; local wisdom; Pancasila education; elementary school; civic awareness